2005
DOI: 10.1021/bi050669o
|View full text |Cite
|
Sign up to set email alerts
|

Alternative Mode of Binding to Phosphotyrosyl Peptides by Src Homology-2 Domains

Abstract: Src homology-2 (SH2) domains recognize specific phosphotyrosyl (pY) proteins and promote protein-protein interactions. In their classical binding mode, the SH2 domain makes specific contacts with the pY residue and the three residues immediately C-terminal to the pY, although for a few SH2 domains, residues N-terminal to pY have recently been shown to also contribute to the overall binding affinity and specificity. In this work, the ability of an SH2 domain to bind to the N-terminal side of pY has been systema… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
11
0

Year Published

2006
2006
2020
2020

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 15 publications
(13 citation statements)
references
References 20 publications
2
11
0
Order By: Relevance
“…3B). Similar differences were consistently observed for the total variance of the coordinates of the N-SH2 C a atoms (SHP2 I42 : 157 Å 2 ; wild-type SHP2: 119 Å 2 ; SHP2 A42 : 85 Å 2 ), implying that the higher peptide mobility was correlated to a higher level of protein fluctuations, particularly in the BC loop (residues 34-40), N-terminal helix (residues [13][14][15][16][17][18][19][20][21][22] and the loop preceding it (residues 9-12) (Fig. 3B).…”
Section: T42a and E139d Amino Acid Substitutions In The N-sh2 And C-sh2 Domainssupporting
confidence: 65%
“…3B). Similar differences were consistently observed for the total variance of the coordinates of the N-SH2 C a atoms (SHP2 I42 : 157 Å 2 ; wild-type SHP2: 119 Å 2 ; SHP2 A42 : 85 Å 2 ), implying that the higher peptide mobility was correlated to a higher level of protein fluctuations, particularly in the BC loop (residues 34-40), N-terminal helix (residues [13][14][15][16][17][18][19][20][21][22] and the loop preceding it (residues 9-12) (Fig. 3B).…”
Section: T42a and E139d Amino Acid Substitutions In The N-sh2 And C-sh2 Domainssupporting
confidence: 65%
“…SHP-1 is composed of two SH-2 domains (N-SH2 and C-SH2) and one catalytic PTP domain (Yang et al, 1998). Studies have shown that the activity of SHP-1 is also regulated by the conformational rearrangement upon substrate/chemical binding: The N-SH2 domain is released from the interaction with the PTP domain exposing the catalytic site of the PTP domain, thereby enhancing SHP-1 activity (Qin et al, 2005;Wang et al, 2011;Yang et al, 2003). Interestingly, we identified that multiangiokinase inhibitor sorafenib also acts as a direct enhancer of SHP-1 (Tai et al, 2011(Tai et al, , 2014b.…”
Section: Introductionmentioning
confidence: 99%
“…Secondly, the regulatory network of SHP-1 with other molecules (tumor suppressors or oncoproteins) that might influence patient prognosis remains to be defined. Moreover, biologically the activity of SHP-1 strongly depends on its structure conformation change (open and close forms), such as ligand and chemicals binding and thus expression levels not necessarily correlated with SHP-1 activities 24 25 26 27 ; however, it is difficult to directly measure SHP-1 activity from archived patient tumor samples. Nevertheless, more studies are necessary to determine the significance of SHP-1 expression in correlation with survival outcome in patients with TNBC.…”
Section: Discussionmentioning
confidence: 99%
“…The activity of SHP-1 strongly depends on the conformational rearrangement through ligand or chemical binding. The interaction between ligands/chemicals and SH2 domains will induce conformational changes of SHP-1, resulting in the releasing of the N-SH2 domain from the PTP domain and initiating the whirling of the C-SH2 domain and further exposing the active site of PTP domain 25 26 27 . Interestingly, we previously reported that regorafenib could directly activate SHP-1 in HCC and CRC, which was independent of its angio-kinase inhibition 28 29 .…”
mentioning
confidence: 99%